1993
DOI: 10.2165/00003495-199345030-00007
|View full text |Cite
|
Sign up to set email alerts
|

Mifepristone

Abstract: Mifepristone is a potent oral antiprogestogen which acts at the level of the receptor, having a high affinity for the progesterone receptor. Most of the clinical trials have studied its efficacy in the termination of early pregnancy when used in conjunction with a low dosage of a prostaglandin analogue. In these studies, mifepristone 100 to 600mg administered as a single dose or over 3 or 4 days, 36 to 48 hours before a prostaglandin analogue given vaginally, intramuscularly or orally, induced complete abortio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(13 citation statements)
references
References 111 publications
1
12
0
Order By: Relevance
“…Activation of type II, but not type I, glucocorticoid receptors contributes to hypertension induced by the agonists (Clapham and Turner, 1997). RU486 is a type II glucocorticoid receptor antagonist that does not bind to type I mineralocorticoid receptors or aldosterone receptors (Brogden et al, 1993). We also recognize that our results showed that GABA A or GABA B receptor antagonist by itself evoked hypotension and bradycardia.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Activation of type II, but not type I, glucocorticoid receptors contributes to hypertension induced by the agonists (Clapham and Turner, 1997). RU486 is a type II glucocorticoid receptor antagonist that does not bind to type I mineralocorticoid receptors or aldosterone receptors (Brogden et al, 1993). We also recognize that our results showed that GABA A or GABA B receptor antagonist by itself evoked hypotension and bradycardia.…”
Section: Discussionsupporting
confidence: 54%
“…These coordinates were selected to cover subdivisions of NTS in which functionally identified barosensitive neurons reside (Chan and Sawchenko, 1998). Test agents used included a synthetic glucocorticoid, Dex (Sigma-Aldrich, St. Louis, MO); a selective glucocorticoid type II receptor antagonist (Clapham and Turner, 1997;Limbourg et al, 2002), mifepristone (RU486; SigmaAldrich), that does not bind to the type I mineralocorticoid receptor or to aldosterone receptors (Brogden et al, 1993); a selective GABA A receptor antagonist (Galvez-Ruano et al, 1995), bicuculline methiodine (Sigma-Aldrich); a GABA B receptor antagonist (Al-Dahan et al, 1990), 2-hydroxy saclofen (2-OH saclofen; Sigma-Aldrich); a nonselective nitric-oxide synthase (NOS) inhibitor (Reif and McCreedy, 1995), N G -monomethyl-L-arginine acetate (L-NMMA; SigmaAldrich); a PI3K inhibitor (Vlahos et al, 1994), LY294002 (Calbiochem, San Diego, CA); and an RNA synthesis inhibitor , actinomycin D (AMD; Calbiochem). The dose and treatment scheme were adopted from previous reports (Clapham and Turner, 1997;Ouyang and Wang, 2000;Hafezi-Moghadam et al, 2002;Limbourg et al, 2002;Moreno et al, 2002;Chan et al, 2003), which used the same test agents for the same purpose as in this study.…”
Section: Methodsmentioning
confidence: 99%
“…These side effects are mostly due to the antiglucocorticoid activity at this high dosage (31). Because RU 486 is used as an agonist in this gene-switch system, we believe that there will be no significant antiglucocorticoid or other deleterious effects at this low dosage in animals or in humans.…”
Section: Resultsmentioning
confidence: 95%
“…The doses of mifepristone needed for induction in our regulatory system (0.1-0.5 mg͞kg) is far below levels at which mifepristone is used as an antiprogestin (10 mg͞kg) together with prostaglandin to terminate pregnancy. Administration of mifepristone at levels much higher than those necessary for transgene induction in our regulatory system have been administered safely to patients on a daily basis to treat different diseases (21,22). Thus, it is likely that mifepristone, at this low concentration, can serve as a potent inducer for human gene therapy, even for a prolonged period of time.…”
Section: Discussionmentioning
confidence: 99%